EPISTEMOLOGI ILMU PENDIDIKAN AGAMA ISLAM: KONSEP EPISTEMOLOGI PERPSEKTIF BARAT DAN ISLAM - Jais Aswanda; Amril; Sawaluddin (STAI Nurul Falah Airmolek, 2024)
This research aims to understand the epistemology of western and Islamic views.Epistemology is a theory of knowledge,related to philosophy can be exemplified like a tree that has branches. The tree then has branches in the form of parts of science: philosophy of science, ethics, aesthetics, philosophical anthropology and metaphysics. Epistemology as part of the branch of philosophy is devoted to sources of knowledge.The method in this research uses library research by collecting data from writings (literacy) that are related to the topic discussed, namely Western and Islamic Perspective Epistemology. The researchers took this data from documentation in the form of books, research journals and supporting articles. The discussion method uses a descriptive-analysis method, namely explaining and elaborating the main ideas relating to the topic being discussed. Then present it critically through primary and secondary library sources related to the theme. Writerexplains three sources of epistemology: empiricism, rationalism, and criticism.The three types of theories of knowledge that are usually mentioned in Muslim thought are as follows: the first is the theory of rational knowledge, with figures such as Al-Farabi, Ibn Sina, Ibn Bajjah, Ibn Tufail, Ibn Rushd, and others. The second is the theory of sensory knowledge, which is limited to the classification of sources of knowledge and no philosopher has developed this theory. The third is a theory obtained through inspiration.